2022
DOI: 10.1161/circinterventions.121.011408
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intracoronary Epinephrine and Adenosine for No-Reflow in Normotensive Patients With Acute Coronary Syndrome (COAR Trial)

Abstract: Background: Intracoronary epinephrine has been effectively used in treating refractory no-reflow, but there is a dearth of data on its use as a first-line drug in normotensive patients in comparison to the widely used adenosine. Methods: In this open-labeled randomized clinical trial, 201 patients with no-reflow were randomized 1:1 into intracoronary epinephrine as the treatment group and intracoronary adenosine as the control group and followed for 1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 27 publications
0
21
0
2
Order By: Relevance
“…We identified 646 articles in the initial search. After removal of duplicates ( n = 116) and excluding ineligible articles (title / abstract: n = 498, full-text: n = 28) and addition of two citations from the Google Scholar survey, six articles met our inclusion criteria; included studies focused on efficacy and safety of IC epinephrine as a first-line treatment ( n = 2) 6 , 11 or after failure of other conventional agents ( n = 4) 7 10 for the treatment of patients with no-reflow phenomenon. Studies were conducted in Egypt ( n = 2), Poland ( n = 1), Pakistan ( n = 1), the United States ( n = 1), and Turkey ( n = 1) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We identified 646 articles in the initial search. After removal of duplicates ( n = 116) and excluding ineligible articles (title / abstract: n = 498, full-text: n = 28) and addition of two citations from the Google Scholar survey, six articles met our inclusion criteria; included studies focused on efficacy and safety of IC epinephrine as a first-line treatment ( n = 2) 6 , 11 or after failure of other conventional agents ( n = 4) 7 10 for the treatment of patients with no-reflow phenomenon. Studies were conducted in Egypt ( n = 2), Poland ( n = 1), Pakistan ( n = 1), the United States ( n = 1), and Turkey ( n = 1) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Khan et al 6 compared the efficacy and safety of IC epinephrine with adenosine for the treatment of the no-reflow phenomenon, mainly after PPCI. They found that patients in the epinephrine group experienced more frequently TFG = 3 (90% versus 78%, respectively) and MBG = 3 (55% versus 45%, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Одним з останніх досліджень з цього приводу було дослідження COAR Trial щодо порівняння інтракоронарного аденозину та адреналіну для лікування ФДМ у пацієнтів з нормальним тиском на тлі ГКС. І висновок був дещо неочікуваним, а саме те, що адреналін безпечний для застосування в пацієнтів з нормальним тиском та, більше того, асоціювався з кращою ефективністю, ніж аденозин за оцінкою кровоплину та міокардіального блашу в разі лікування no-reflow [21]. Ми знаємо, що адреналін дає позитивний хронотропний та інотропний ефекти, але саме через бета-2-адренорецептори опосередковується його дія у вигляді коронарної вазодилатації.…”
unclassified